Bedah Kisi-Kisi Olimpiade IPA pada Materi Besaran, Satuan dan Pengukuran Melalui Media YouTube - Aji Saputra; Hijrasil Hijrasil; Sumarni Sahjat; Nurlaela Muhammad; Hutri Handayani Isra; Masrifah Masrifah; Indah Kristiani Siringo Ringo; Dewi Amiroh; Mirda Prisma Wijayanto; Andy Hermawan; Palti Maretto Caesar Manalu; Hilya Wildana Sofia; Riris Idiawati; Khoironi Fanana Akbar; Ferdiana Ferdiana; Nurul Hidayah (Universitas Maritim AMNI Semarang, 2025)
This activity aims to analyze the results of the study of Science Olympiad content outline on the subject of Quantities, Units and Measurement. This video was made using the PowerPoint application for the content, and the Ice Cream screen recorder to record. The research method uses a descriptive qualitative method with a sample of all viewers, the majority of whom are junior high school students. This activity can be concluded as effective by looking at the number of viewers reaching more than 28 thousand, the number of likes 920 without dislikes and 40 positive comments from viewers who accessed on March 12, 2025 at 21:37.